2016
DOI: 10.18632/oncotarget.10335
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of serum hepatitis B virus load in the carcinogenesis and prognosis of hepatocellular carcinoma: evidence from two meta-analyses

Abstract: Background and AimThe meta-analysis aimed to quantify and summarize the contribution of serum hepatitis B virus (HBV) DNA load in the carcinogenesis and prognosis of hepatocellular carcinoma (HCC).ResultsNine independent studies with a total of 1162 cases and 9365 participants on risk of HCC and seventeen studies with 1342 cases and 2891 participants on recurrence of HCC were finally included. The non-liner dose-response association between HBV DNA level and HCC risk was observed, with P value equal to 0.02 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) ranks the sixth most common cancer and the third cause of cancer-related mortality worldwide [ 1 , 2 ]. In Asia and sub-Saharan Africa areas, over 5% of the populations suffered chronically infected chronic hepatitis B virus (HBV) infection, which could reflect the elevated prevalence of HCC [ 1 , 3 5 ]. In china, the estimated new cases and deaths for HCC were 466.1 and 422.1 thousands, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) ranks the sixth most common cancer and the third cause of cancer-related mortality worldwide [ 1 , 2 ]. In Asia and sub-Saharan Africa areas, over 5% of the populations suffered chronically infected chronic hepatitis B virus (HBV) infection, which could reflect the elevated prevalence of HCC [ 1 , 3 5 ]. In china, the estimated new cases and deaths for HCC were 466.1 and 422.1 thousands, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These were largely in line with the results of the previous studies . In particular, the Taiwan REVEAL‐HBV study, the Jiangsu Qidong cohort study and a meta‐analysis reported dose‐dependent relationship between HBV DNA and increased liver cancer risk, then a decrease in magnitude of the association in the highest DNA level groups, which is in concordance with our observations. On the other hand, as another major viral cause of liver cancer worldwide especially in western countries, (4) HCV infection showed a very low prevalence in this population, and there is no significant association detected between HCV and liver cancer in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens stimulate virus replication and transcription in males causing a higher viral load which is associated with an increased risk of occurrence of HCC [13] . In fact, high HBV-DNA serum levels have been reported to be associated with a nonlinear doseresponse to a higher incidence and recurrence of HCC [14] . Furthermore, it has been reported that estrogens appear to act as protectors towards the development of HCC [15] .…”
Section: Hcc and Hbv Chronic Infectionmentioning
confidence: 99%
“…As mentioned above, high viral loads, as well as a seropositive status of HBe antigen (HBeAg) are associated with a higher risk of developing HCC [14] . It has been reported that HBeAg seropositive patients has a relative risk of HCC of 60.2 compared to 9.6 of those seronegative [27] .…”
Section: Hcc and Hbv Chronic Infectionmentioning
confidence: 99%